Dose-response effects of in-feed antibiotics on growth performance and nutrient utilization in weaned pigs fed diets supplemented with yeast-based nucleotides - Samuel M. Waititu; Jung M. Heo; Rob Patterson; Charles M. Nyachoti (Animal Nutrition, 2015)
Dietary nucleotides are bioactive compounds with the potential to mitigate weaning-associated challenges in piglets. An experiment was conducted to determine the interaction effect of antimicrobial growth promoters (AGP) and a nucleotide-rich yeast extract (NRYE) on growth performance and apparent total tract digestibility (ATTD) of dry matter (DM), crude protein (CP) and gross energy (GE), and to establish whether NRYE supplementation may completely or partially replace AGP in diets for weaned pigs. In phase 1 and 2, corn, wheat, canola meal and soybean meal based diets, which were formulated to contain 0.0 or 0.1% NRYE with 0, 25, 50, 75 or 100% of the recommended AGP dosage, were fed to 108 twenty-one day old piglets (initial body weight 7.11 ± 0.9 kg; mean ± SD) from d 1 to 14 and 15 to 28, respectively. Overall, increasing AGP level in NRYE supplemented diets linearly decreased average daily gain (ADG) (P = 0.002) and gain-to-feed ratio (G:F) (P = 0.007); and quadratically decreased ATTD of DM (P = 0.001), CP (P = 0.003) and G:F (P = 0.017) during phase 2. Compared with control and pigs fed NRYE with 100% of recommended AGP dosage, pigs fed 0.1% NRYE without AGP had greater (P < 0.05) ADG and G:F in phase 2 and overall. In conclusion, supplementing 0.1% NRYE improved growth performance of pigs but this beneficial effect was reduced by increasing dietary AGP dosage. Keywords: Antimicrobial growth promoters, Digestibility, Growth performance, Piglet, Nucleotide-rich yeast extract